A construção do currículo e o ofício de professor na transformação cidadã e na história de vida de estudantes de uma comunidade da cidade de São Paulo - Jesus, Marcelo Donatti de (2021)
The following study aims at investigating the pedagogical initiatives developed in the community of Paraisópolis and its vicinity, from a democracy proposal for a curriculum developed in so-called “Escola da Comunidade (E. C.)” – Community School – in a social program maintained for decades by a traditional school in southern São Paulo City, Brazil – together with the pedagogical performance of an educator committed to his professionalism in the process of building autonomy and critical awareness of the students in question. From testimonies given by former students who, from 2016 to 2019, took part in the educational process analysed here, the study uses qualitative approach – which allows researchers who study within their natural contexts to better understand and interpret phenomena in terms of meaning that people attribute to them – and the reality of the researcher in order to show that a democratic curriculum is capable of transforming the reality of the students of the “Escola da Comunidade” in a profound and citizenly way, provided it is lived through inside and outside the classroom and carried out in a professional and systematized way by an educator involved with the world of education. Especially supported by theoretical approach favoured by professor and thinker Paulo Freire and by the luminous critical reflections aroused and proposed by professor and writer José Gimeno Sacristán, this study aims at explaining the citizenly transformation of the students of the aforementioned social program through a curriculum that is discussed and heedful of the needs of the different voices that are part of it, carried out in a permanent, reflective and professional way by an educator together with partners connected to pedagogical strategies and initiatives that mind, respect and transform all participants in the educational process